Affective Organizing: Collectivizing Informal Sex Workers in an Intimate Union. (February 2019) - Hardy, Kate; Cruz, Katie
As informal, self-employed workers, street sex workers are frequently understood as a "hard-to-organize" group. As they are not legally registered or protected, they are excluded from institutional arrangements for unionization and collective bargaining and from access to both labor and social protections, due to the lack of recognition of the work they undertake. Despite this, sex workers in Argentina have been successful in generating solidarity and class consciousness as a basis for collective action. To do so, we argue that AMMAR (Asociación de Mujeres Meretrices de Argentina), the Argentinean sex workers' union, has used a strategy of "affective organizing." Drawing on a participatory project developed with and involving sex worker activists from AMMAR, the article examines 108 interviews, questionnaires, and participant observations. Overall, we argue for greater attention to be paid by scholars working in the fields of the sociology of work and employment and industrial relations, attention to emotion and affect as their foundational role in labor organizing and collective action. Overall, it is posited that the practices of AMMAR in one of the most stigmatized sectors of the labor market hold invaluable lessons for locating relationality and care at the center, rather than the margins, of labor movements as a basis for the wider transformation of social relations in capitalism.